Tree species distribution in tropical peatland forest along peat depth gradients: Baseline notes for peatland restoration - Dwi Astiani; HANNA ARTUTI EKAMAWANTI; WIWIK EKYASTUTI; TRI WIDIASTUTI; GUSTI EVA TAVITA; MURTI ANOM SUNTORO (Society for Indonesian Biodiversity, 2021)
Abstract. Astiani D, Ekamawanti HA, Ekyastuti W, Widiastuti T, Tavita GE, Suntoro MA. 2021. Tree species distribution in tropical peatland forest along peat depth gradients: Baseline notes for peatland restoration. Biodiversitas 22: 2571-2578. Tropical peatland forest is a unique and fragile ecosystem. It is composed of peat with a depth of 30 cm to 17 m, and plays an essential role in maintaining an appropriate environment balance both as a water reservoir, sink and carbon storage, climate change, and support system for regional biodiversity, which is currently increasingly threatened. A study has been completed to examine peatland forest tree diversity in the gradients of peat depth found on the peatland fringe toward the center of the peat dome and the other side of the peatland perimeter in Sungai Besar peatland forest group in Ketapang West Kalimantan. Twenty-six plots measuring 20 ×100 m were sampled to identify the tree species with a diameter above 5 cm along an 18 km transect length. The trees' assessment was accomplished using a systematic line plots method, where peat depth-plot repetitions were measured by producing 'fishbone' transects perpendicular to the main transect. Peat depths were assessed on plots measured. Results indicate that there were 79 tree species in overall peatland sites measured. It is found that peat depth has impacted tree species distribution on peatland. There was a shift of some tree species with peat depth changes. Along with peat depth range from 0.5 to 10 m, some species were found to be abundant on a more extensive range of peat depth, such as perepat (Combretocarpus rotundatus), mentibu (Dactylocladus stenotachys), and bintangur (Calophyllum rigidum), while other were not. Some species were only found in shallow peat, and some were solely available in the deeper ones. It was found that peat depth could determine tree species distribution in peatland forests.